Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jfpp.13752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autochthonous Pediococcus acidilactici on volatile profile and some properties of heat-treated sucuk

Abstract: The possibility of using Pediococcus acidilactici S147 as a starter culture in heat‐treated sucuk production has been investigated in the research. P. acidilactici S147 showed a good growth during fermentation and caused a rapid pH drop. In the starter culture group, a decrease in lactic acid bacteria count was determined by about 1 log unit during the heat treatment. In Microccoccus/Staphylococcus count, less reduction was observed during the heat treatment than the lactic acid bacteria count. In the final pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The different internal temperature application had no significant effect on these microorganisms. Yılmaz (2016) and Öz et al (2018) also found similar results. In the present study, Enterobacteriaceae count was found to be below the detectable limit (<2 log cfu/g) at all stages, including the sucuk batter.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The different internal temperature application had no significant effect on these microorganisms. Yılmaz (2016) and Öz et al (2018) also found similar results. In the present study, Enterobacteriaceae count was found to be below the detectable limit (<2 log cfu/g) at all stages, including the sucuk batter.…”
Section: Resultssupporting
confidence: 52%
“…This result showed that the thermal resistance of P. acidilactici S147, which was used as the starter culture, was high. Indeed, Öz et al (2018) also determined that P. acidilactici S147 strain was heat resistant. In other studies on heat‐treated sucuk, different levels of reductions were observed in lactic acid bacteria count during the heat treatment (Çakır et al, 2013; Ercoşkun, 2006; Kaban & Bayrak, 2015; Yılmaz, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although the alcohol abundance increased as the BG usage rate increased, there was no statistical difference between the BG-1%, BG-2%, and BG-3% groups (Figure 2). In previous studies on HTS, among alcohols, ethanol was found to be the most abundant compound [8,[18][19][20], which is a product of carbohydrate metabolism [21]. Furthermore, 1-propen-2-ol was identified in HTS by Sallan et al [8] and Öz et al [20].…”
Section: Volatile Compoundsmentioning
confidence: 97%
“…A study reports that an autochthonous P. acidilactici S147 strain when introduced as a starter culture in heat‐treated sucuk, a traditional Turkish semi‐dry fermented sausage, it significantly reduced the spoilage Micrococcus/ Staphylococcus spp. counts (Öz et al., 2018. Therefore, finding out potential strains that could produce both the antibacterial and antifungal compounds has a strict significance in industrial perspectives and food preservation aspects.…”
Section: Introductionmentioning
confidence: 99%